Ministry of Health and private maize industry in Kenya initiate systematic aflatoxin surveillance - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Plan for systematic aflatoxin surveillance of packaged and bulk maize, jointly designed by the Ministry of Health, Cereal Millers Association of Kenya, IFPRI, and the University of Nairobi.